Consumo, digestibilidade, produção e composição do leite de vacas alimentadas com silagem de grão de milho moído reidratado substituindo milho seco moído do concentrado - Igor Alves Pereira Mendes (2013)
This study aimed to evaluate the substitution of dry ground corn by rehydrated ground corn silage as fed or as dry matter basis in the diet of dairy cows on intake, digestibility, milk production and composition. A total of 12 multiparous Holstein cows were used. Nine cows averaging DEL 90 days, weighting 549 kg and producing 34 kg of milk / day in three simultaneous designs 3x3 Latin square. In addition, 3 cows were rumen cannulated to measure ruminal pH, ammonia nitrogen and volatile fatty acids. The control diet was based on corn silage and dry ground corn in the concentrate (MGSM). The other diets were based on corn silage and the dry ground corn silage of the concentrate was replaced by rehydrated ground corn silage in dry matter basis (MRMS) or as fed basis (MRMN). The dry matter intake differed (P <0.05) among treatments, being higher for MGSM. Feed efficiency was better (P <0.05) for the MRMN treatment. Replacement of the dry ground corn by rehydrated corn silage as fed basis presented itself as the best diet and has the advantage of using less corn in the diet.